Teknik Dasar Pengambilan dan Pengolahan Fotografi Produk Kerajinan Tangan Pada Badan Usaha Milik Desa Dagang - Imam Saputra; Rivalri Kristianto Hondro; Alwin Fau (Jurnal ABDIMAS Budi Darma, 2020)
Kerawan Dagang BUMDes has long been established and has several superior products in the form of handicrafts in the form of flowers made from plastic waste. With this superior product, trading voluntary villages should be able to further develop BUMDes for the welfare of their village communities. At present, the handicraft is still placed in a shop window, so it is very limiting for people who want to see it. Some have used social media to sell these handicraft products. This has a positive impact because the reach of people who can see becomes wider. But the display of photos of the product is less attractive because it still uses makeshift cameras and does not use techniques for taking photos of products such as lighting that is less than optimal. With the dedication to the community with the theme of the Basic Technique of Taking and Processing Handicraft Product Photography at the Tanjung Morawa Cluster Business Village Ownership, it is expected to increase sales of these handicraft products.